PEMANFAATAN GAMBAR SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN MENYULAM, PESERTA DIDIK KELAS VII.2 DI SMPN 2 X KOTO TANAH DATAR - MIRA MAKHNETIS, Drs. Syafwan, M.Si, Dra. Jupriani, M.Sn (Serupa The Journal of Art Education, 2014)
This article aims to improve the ability and understanding oflearners in embroidering with the formulation of research objectives"to improve the ability of learners classroom embroider VII2 SMP 2 XKoto Tanah Datar by using images as a medium of learning".This research is a class act that is performed by 2 cycles. Datacollection was conducted through embroider ability tests andobservation of teacher activity. This study used a qualitative andquantitative approach. Subjects were VII2 grade students of SMP N 2X Koto Tanah Datar.The result showed that media images can improve the abilityembroider learners with learning activities of three phases: (1) initialactivity, (2) the core activities, and (3) the end of the activity. Fromprocessing the data obtained from studies conducted pemebelajaranimplementation learners seen an increase in the ability to embroider. itis thus that the use of media images can improve the ability embroiderVII2 grade students of SMP N 2 X KotoTanah Flat.Keywords: Use of images, instructional media, the ability toembroider, learners